Modelling the dry-contact interface of rigid blocks under torsion and combined loadings: Concavity vs. convexity formulation. (March 2018) - Casapulla, C.; Maione, Alessandra
Abstract: The definition of the yield domains within the limit analysis of 3D dry-jointed masonry block structures requires experimental and analytical investigation on the frictional contact conditions. One of the aspects which still create some challenging analysis problems yet to be fully resolved is related to the modelling of the geometric contacts accounting for the interaction of normal and shear forces, torsion and bending moments. In particular, a great difference in torsion capacity can be found within the single contact surface when adopting the most used models, i.e. those based on the concave and convex contact formulations. In this paper a comparison between these two formulations for the yield domains of pure torsion and combined loadings is carried out in order to identify the most reliable assumptions on the contact model. For both formulations, the analytical model of two dry-stacked rigid blocks is adopted under the assumptions of infinite compressive strength for blocks and no-tension and frictional behaviour at their contact. The results are also compared with experimental outcomes and other analytical results existing in the literature and difference percentages are evaluated in terms of torsion strengths. Lastly, a simple criterion to correct the torsion capacity provided by the concavity model is proposed, together with its implication on each case of combined loadings, in order to achieve a better agreement with the experimental data and the convexity formulation. Highlights: Masonry assemblages of rigid blocks with frictional contact interfaces were considered. Difference in torsion capacity was found by comparing concavity and convexity models. The difference in torsion capacity also affects the torsion-shear-flexure interaction. A reliable and simple correction of the concavity formulation was proposed. The proposed formulation was validated against analytical and experimental results.